Local social and environmental impacts of biofuels: Global comparative assessment and implications for governance - German, L.; Schoneveld, George C.; Pacheco, P. (2011)
The 2000s witnessed the rapid expansion of biofuel plantations in the global South in the context of a growing trend of crop plantation expansion. This trend has been spurred by policies in the European Union, United States, Brazil, and other countries favoring the use of biofuels in the transport sector to enhance energy security and reduce carbon emissions, as well as by the desire of governments in developing countries to harness the stimulus that new commercial investments provide to the agricultural sector and to national economies. Despite these potential benefits, a number of concerns have been raised about the local social and environmental impacts of biofuel feedstock expansion. We shed light on this debate through a synthesis of findings from case studies in six biofuel producer countries of Asia, Africa, and Latin America, and a seventh paper exploring the implications of the land-use changes observed in these case studies for the climate mitigation potential of biofuels. We also explore the implications for governing the environmental impacts of biofuel feedstock production, protecting the rights of customary land users, and enabling smallholder-inclusive business models. Our analysis suggests that better governance of the sector’s impacts is not the exclusive preserve of unitary sets of actors, but instead requires concerted and coordinated efforts by governments of producer and consumer countries, investors, civil society, and the financial sector to better capture the sector’s potential while minimizing its social and environmental costs.